ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT KIMIA FARMA TBK PERIODE 2017-2022 - Pakpahan, Andre Yahya; Rioni, Yunita Sari (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The Research was entitled “Financial Report Analysis to Assess Financial Performance at PT Kimia Farma Tbk for the 2017-2022”. The aims of the research is to assess the financial performance of PT Kimia Farma Tbk by measuring liquidity ratios and profitability ratios. The type data used is secondary data in the form of financial position report and profit and loss statement for the period 2017-2022. The data collection using documentation techniques downloaded from the companys official website. The data analysis techniques used are ratio analysis and descriptive statistical analysis.The result of the research show that the financial performace of PT Kimia Farma Tbk period 2017-2022 is an a fluctuating state that tends to decline. Overall the level of liquidity ratios and profitability ratios are in the poor category because all ratios are below the industry average ratio